Peran Orang Tua Dan Keluarga Dalam Menghadapi Tantangan Etika Remaja Kristen Di Era Teknologi Digital - Hendrikson Febri; Amoli Ndraha; Erni Dethan; Korina Sanosa; Piter Imanson Damanik (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
As time advances, digital technology has gradually become contaminated with Christian teenagers. Instead of digital technology helping in the process of accelerating "practical life", now it instead hinders the mind which leads to a blur of good and bad "ethical" values. The method used in this research is a qualitative method with a library research approach by analyzing textbooks. Christian ethical education and its concrete implementation by parents and families play an important role in facing the challenges of advances in digital technology. The results of this research are, 1) Parents and families who educate their children with the truth of God's word, they carry out God's commands by being responsible for the gift that God has given, namely "their children". 2) Parental education which is based on God's Word, becomes an ethical alarm in teenagers, so that teenagers can wake up and be reminded to use digital technology well.